156k views
1 vote
Multiply (u-6w-2)(2u+5w)

1 Answer

6 votes

Answer:


=2u^2-7uw-30w^2-4u-10w

Explanation:


\left(u-6w-2\right)\left(2u+5w\right)\\Distribute\:parentheses\\=u\cdot \:2u+u\cdot \:5w+\left(-6w\right)\cdot \:2u+\left(-6w\right)\cdot \:5w+\left(-2\right)\cdot \:2u+\left(-2\right)\cdot \:5w\\Apply\:minus-plus\:rules\\+\left(-a\right)=-a\\=2uu+5uw-6\cdot \:2uw-6\cdot \:5ww-2\cdot \:2u-2\cdot \:5w\\\mathrm{Simplify}\:2uu+5uw-6\cdot \:2uw-6\cdot \:5ww-2\cdot \:2u-2\cdot \:5w:\quad 2u^2-7uw-30w^2-4u-10w\\=2u^2-7uw-30w^2-4u-10w

User Mark Manickaraj
by
6.2k points